Diketopyrrolopyrrole-based acceptors with multi-arms for organic solar cells. Issue 44 (12th July 2018) - Sun, Po; Li, Xiangzhi; Wang, Yulong; Shan, Haiquan; Xu, Jiaju; Liu, Changmei; Zhang, Cong; Chen, Fei; Xu, Zongxiang; Chen, Zhi-kuan; Huang, Wei
Abstract : Three diketopyrrolopyrrole-based small molecule acceptors consisting of a spirobifluorene (SBF) core unit and diketopyrrolopyrrole dicyanovinyl (DPPDCV) units as the arms have been synthesized for organic solar cells. Abstract : Three small moleculesSBF-1DPPDCV, SBF-2DPPDCV andSBF-4DPPDCV consisting of a spirobifluorene (SBF) unit as the core and one, two, and four diketopyrrolopyrrole dicyanovinyl (DPPDCV) units as the arms have been designed and synthesized for solution-processed bulk-heterojunction (BHJ) solar cells. The UV-Vis absorption and cyclic voltammetry measurement of these compounds showed that all these compounds have an intense absorption band over 300–750 nm with a LUMO energy level at around −3.87 eV. When pairing with PTB7-Th as the donor, devices fabricated based on PTB7-Th : SBF-4DPPDCV blends showed a decent PCE of 3.85%, which is the highest power conversion efficiency (PCE) amongst the three DPP acceptor fabricated devices without extra treatment. Devices withSBF-1DPPDCV andSBF-2DPPDCV acceptors showed lower PCEs of 0.26% forSBF-1DPPDCV and 0.98% forSBF-2DPPDCV respectively. The three dimensional (3D) structure ofSBF-4DPPDCV facilitates the formation of a 3D charge-transport network and thus enables a rational electron-transport ability (1.04 × 10 −4 cm 2 V −1 s −1 ), which further leads to a higher J sc (10.71 mA cm −2 ). These findings suggest that multi-arm acceptors present better performance than one-arm or two-arm molecules for organic solar cells.